(untitled) (Journal of Economic Research & Business Administration, 2019)
The article analyzes the problems of economic security. Economic security is the state of the national economy that provides for the satisfaction of the country’s vital needs for material goods, regardless of the occurrence of force majeure of a socio-political, economic or environmental nature in the global economic system or within the country. Ensuring economic security in the state, as well as any economic entity in Russia has a significant role, is implemented through the mechanism of economic security, which acts as a system of measures to prevent economic threats (economic monitoring, forecasting, detection and prevention of threats, the definition of limit (threshold) indicators). Economic security in the era of globalization is an important component of national security, as the economy permeates all spheres of activity of the state. The authors investigate the evolutionary trend of modern society in the era of globalization. In a single economic space globalization acts as a new level of economic activity. In the context of globalization, despite the existing risks, challenges and threats to economic security, it is necessary to take into account the factors of strengthening the national economy and increasing its competitiveness. The article analyzes the threats to the economic security of Russia. Today, the Russian economy is under the pressure of sanctions, which poses a threat to its stabilization so ensuring economic security is one of the key conditions for its consolidation. In the state of economic security, sustainable economic growth is ensured, as well as the protection of the country’s economic interests at all levels: national and international. Threats to economic security are phenomena and processes that have a negative impact on the economy of the country, infringing on the economic interests of the individual, society and the state.